Review Of Metabolic Syndrome: A Rising Menace - DR. DIPTI MOHAPATRA,; DR. PRAKASH KR. SASMAL, (International Journal of Pharma and Bio Sciences, 2011)
The prevalence of obesity, a major risk factor of metabolic syndrome is increasing in frightening proportions worldwide in all the age groups. Multiple diseases or co-morbidities associated with obesity are termed the “Metabolic Syndrome,” or “Syndrome X”. Resistance to insulin is the central feature of the metabolic syndrome. Increased tendency to develop central obesity makes Asian Indians prone to develop metabolic syndrome, which has resulted in the growing epidemic of type 2 diabetes and coronary heart disease currently sweeping the Indian subcontinent. The current modalities of treatment of metabolic syndrome include diet, exercise and pharmacotherapy. Life-style modification programmes that promote daily physical activity and healthy eating devoid of saturated fat and processed carbohydrate are desperately needed to tackle this growing menace. Using Bariatric surgery explicitly to treat metabolic disorders including diabetes is a revolutionary concept and represents a disruption to current therapeutic paradigms.